INFLUENCE OF COLD PLASMA JET CONSTRUCTION IRRADIATION ONTO GROUPS OF STAPHYLOCOCCUS AND ESCHERICHIA COLI FOR HUMAN SKIN - Kadhim A. Aadim; Ghaith H. Jihad (Scholar Express Journals, 2021)
Cold atmospheric pressure plasma jets were capable of generating cold plasma plumes that were not confined by electrodes, which make them very enticing for biological, medical and polymer applications. A direct-current, cold atmospheric-pressure Argon plasma microjet (PMJ) was performed to inactivate Staphylococcus aureus (S. aureus) and Escherichia coli (E. coli) in air. The process of sterilization and morphology of bacteria was observed. We wish to know the possible inactivation mechanisms of PMJ and explore a potential application in dental and other temperature sensitive treatment. In this study, we employed a direct current, atmospheric pressure, cold Argon-gas to inactivate bacterias .electronic image was employed to evaluate the morphology of S. aureus and showed rupture of groups after the plasma treatment. During this work, experimental study of a low frequency, atmospheric plasma-jet discharge in argon has been presented. The experimental operation of this device was conducted with commercially Argon power supply. The discharge process operated by using Argon as input gas with different Voltages and different metals (Sn , Cu, Pb). The inactivation rates could reach 100% in 5 min. When the distance between the exit nozzle of the PMJ device and Petri dish was about 1.5cm , effective inactivation was also observed with a similar inactivation curve. The inactivation of bacteria is attributed to the abundant reactive oxygen and nitrogen species, as well as ultroviolet radiation in the plasma. Different life spans and defensibilities of these killing agents may hold the key to understanding the different inactivation curves at different treatment distances.
Keywords: Scholars of the locality of Al-Harbiya; the locality of Al-Harbiya Baghdadi; the intellectuals of the locality of Al-Harbiya